Nivolumab monotherapy in recurrent metastatic urothelial carcinoma (CheckMate 032): a multicentre, open-label, two-stage, multi-arm, phase 1/2 trial. Issue 11 (November 2016) - Sharma, Padmanee; Callahan, Margaret K; Bono, Petri; Kim, Joseph; Spiliopoulou, Pavlina; Calvo, Emiliano; Pillai, Rathi N; Ott, Patrick A; de Braud, Filippo; Morse, Michael; Le, Dung T; Jaeger, Dirk; et al.
Summary: Background: Few effective treatments exist for patients with advanced urothelial carcinoma that has progressed after platinum-based chemotherapy. We assessed the activity and safety of nivolumab in patients with locally advanced or metastatic urothelial carcinoma whose disease progressed after previous platinum-based chemotherapy. Methods: In this phase 1/2, multicentre, open-label study, we enrolled patients (age ≥18 years) with urothelial carcinoma of the renal pelvis, ureter, bladder, or urethra at 16 sites in Finland, Germany, Spain, the UK, and the USA. Patients were not selected by PD-L1 expression, but tumour PD-L1 membrane expression was assessed retrospectively. Patients received nivolumab 3 mg/kg intravenously every 2 weeks until disease progression or treatment discontinuation because of unacceptable toxicity or other protocol-defined reasons, whichever occurred later. The primary endpoint was objective response by investigator assessment. All patients who received at least one dose of the study drug were included in the analyses. We report an interim analysis of this ongoing trial. CheckMate 032 is registered with ClinicalTrials.gov, NCT01928394 . Findings: Between June 5, 2014, and April 24, 2015, 86 patients with metastatic urothelial carcinoma were enrolled in the nivolumab monotherapy group and 78 received at least one dose of treatment. At data cutoff (March 24, 2016), the minimum follow-up was 9 months (median 15·2 months, IQR 12·9–16·8). A confirmed investigator-assessed objective response was achieved in 19 (24·4%, 95% CI 15·3–35·4) of 78 patients. Grade 3–4 treatment-related adverse events occurred in 17 (22%) of 78 patients; the most common were elevated lipase (four [5%]), elevated amylase (three [4%]), and fatigue, maculopapular rash, dyspnoea, decreased lymphocyte count, and decreased neutrophil count (two [3%] each). Serious adverse events were reported in 36 (46%) of 78 patients and eight (10%) had a serious adverse event judged to be treatment related. Two (3%) of 78 patients discontinued because of treatment-related adverse events (grade 4 pneumonitis and grade 4 thrombocytopenia) and subsequently died. Interpretation: Nivolumab monotherapy was associated with a substantial and durable clinical response and a manageable safety profile in previously treated patients with locally advanced or metastatic urothelial carcinoma. These data support further investigation of nivolumab monotherapy in advanced urothelial carcinoma. Funding: Bristol-Myers Squibb.